2023
DOI: 10.3389/fpls.2023.1107705
|View full text |Cite
|
Sign up to set email alerts
|

Application of potassium nitrate and salicylic acid improves grain yield and related traits by delaying leaf senescence in Gpc-B1 carrying advanced wheat genotypes

Abstract: Grain protein content (GPC) is an important quality trait that effectively modulates end-use quality and nutritional characteristics of wheat flour-based food products. The Gpc-B1 gene is responsible for the higher protein content in wheat grain. In addition to higher GPC, the Gpc-B1 is also generally associated with reduced grain filling period which eventually causes the yield penalty in wheat. The main aim of the present study was to evaluate the effect of foliar application of potassium nitrate (PN) and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…High-confidence MTAs identified through GWAS serve as potential targets for extracting CGs associated with the trait of interest. Several studies utilized GWAS-identified MTAs to extract the potential CGs associated with: (i) agronomic traits including days to anthesis, days to maturity, tiller number, spike length, spikelet number, grain number per spike, grain weight, and grain yield ( Gill et al., 2022 ; Gudi et al., 2024 ); (ii) physiological traits such as chlorophyll fluorescence, chlorophyll content, vegetation index, gas exchange, and stomatal conductance ( Hamdani et al., 2019 ; Gudi et al., 2023 ); (iii) stress tolerance such as drought, heat, salinity, etc ( Tanin et al., 2022 , Tanin et al., 2023 ; Tian et al., 2023 ); (iv) biochemical compounds such as proline, abscisic acid, and hydrogen peroxides (H 2 O 2 ) ( Verslues et al., 2014 ; Kamruzzaman et al., 2022 ); and (v) quality traits including grain protein content, sedimentation volume, kernel hardiness, solvent retention capacity, Fe content, and Zn content ( Gudi et al., 2022b ; Halladakeri et al., 2023 ). Similarly, in the present study we used 13 high-confidence MTAs explaining >10% phenotypic variance and having the LOD scores >5 to extract 216 CGs models.…”
Section: Discussionmentioning
confidence: 99%
“…High-confidence MTAs identified through GWAS serve as potential targets for extracting CGs associated with the trait of interest. Several studies utilized GWAS-identified MTAs to extract the potential CGs associated with: (i) agronomic traits including days to anthesis, days to maturity, tiller number, spike length, spikelet number, grain number per spike, grain weight, and grain yield ( Gill et al., 2022 ; Gudi et al., 2024 ); (ii) physiological traits such as chlorophyll fluorescence, chlorophyll content, vegetation index, gas exchange, and stomatal conductance ( Hamdani et al., 2019 ; Gudi et al., 2023 ); (iii) stress tolerance such as drought, heat, salinity, etc ( Tanin et al., 2022 , Tanin et al., 2023 ; Tian et al., 2023 ); (iv) biochemical compounds such as proline, abscisic acid, and hydrogen peroxides (H 2 O 2 ) ( Verslues et al., 2014 ; Kamruzzaman et al., 2022 ); and (v) quality traits including grain protein content, sedimentation volume, kernel hardiness, solvent retention capacity, Fe content, and Zn content ( Gudi et al., 2022b ; Halladakeri et al., 2023 ). Similarly, in the present study we used 13 high-confidence MTAs explaining >10% phenotypic variance and having the LOD scores >5 to extract 216 CGs models.…”
Section: Discussionmentioning
confidence: 99%
“…First, the foliar application of these components during heading and grain filling stages helps the flag leaf survive longer and delays early leaf senescence. This leads to better grain numbers, grain weight, and TGW, which are main components for final grain yield [ 73 , 74 , 75 ]. Second, the foliar application of these components at later stages facilitates the remobilization of assimilates from the leaves and stems to the grains, resulting in increased grain weight and TGW [ 76 ].…”
Section: Discussionmentioning
confidence: 99%